DETEKSI CEMARAN BAKTERI Eschericia Coli PADA DAGING AYAM BROILER DI UPT LABORATORIUM KESEHATAN HEWAN DINAS PETERNAKAN PROVINSI JAWA TIMUR DI TUBAN - Nadia Puspita Maya; Kuntum Febriyantiningrum; Mahdi Selomashar; Nia Nurfitria (Binar – Biology Natural Resources Journal, 2023)
Food safety is the main demand of consumers. Food quality and safety must be ensured to be free from pathogenic materials and safe for consumption. One of the pathogenic bacteria found as contaminants in broiler chicken meat is the Escericia coli. Broiler meat products that are accepted and that will be consumed by the community, they must meet the specified requirements and be proven by a certificate of test results from a recognized institution and based on ISO 17025. One of the testing agencies that has been accredited by the Komite Akreditasi Nasional (KAN), namely the UPTD Laboratorium Kesehatan Hewan Dinas Peternakan Provinsi Jawa Timur Livestock Service, provides community services in laboratory examinations for testing microbial contamination in animal products (meat, milk and eggs) with quality reference standards for microbial contamination limits according to SNI 7388: 2009. The method used in this study is to use the MPN method. This study used 2 samples of broiler chicken meat from PT. Trijaya Lestari Food. The MNP method is a method used to determine the calculation and estimate the amount of contamination of Escherichia coli bacteria contained in broiler chicken meat samples. The result obtained from this study is that the number of positive tubes shows the MPN value as the amount of Escherichia coli per ml / per g. For dilutions 10ˉ¹, 10ˉ² and 10ˉ³ are valued at 0 and if added up the value is <3.0 which indicates that broiler chicken meat samples are below the maximum contamination limit of the number of Escerichia coli bacteria based on SNI 01-3924-2009.